Immunostaining of Lgr5, an Intestinal Stem Cell Marker, in Normal and Premalignant Human Gastrointestinal Tissue - Laren Becker; Qin Huang; Hiroshi Mashimo (The Scientific World Journal)
Lgr5 has recently been identified as a murine marker of intestinal stem cells. Its expression has not been well characterized in human gastrointestinal tissues, but has been reported in certain cancers. With the increasing appreciation for the role of cancer stem cells or tumor-initiating cells in certain tumors, we sought to explore the expression of Lgr5 in normal and premalignant human gastrointestinal tissues. Using standard immunostaining, we compared expression of Lgr5 in normal colon and small intestine vs. small intestinal and colonic adenomas and Barrett's esophagus. In the normal tissue, Lgr5 was expressed in the expected stem cell niche, at the base of crypts, as seen in mice. However, in premalignant lesions, Lgr5+ cells were not restricted to the crypt base. Additionally, their overall numbers were increased. In colonic adenomas, Lgr5+ cells were commonly found clustered at the luminal surface and rarely at the crypt base. Finally, we compared immunostaining of Lgr5 with that of CD133, a previously characterized marker for tumor-initiating cells in colon cancer, and found that they identified distinct subpopulations of cells that were in close proximity, but did not costain. Our findings suggest that (1) Lgr5 is a potential marker of intestinal stem cells in humans and (2) loss of restriction to the stem cell niche is an early event in the premalignant transformation of stem cells and may play a role in carcinogenesis.